The Relationship Between Temperament, Gender, and Childhood Dysfunctional Voiding. (August 2013) - Colaco, Marc; Dobkin, Roseanne D.; Sterling, Matthew; Schneider, Dona; Barone, Joseph
Objective . Dysfunctional voiding (DV) is an extremely common pediatric complaint. The goal of this study was to examine the relationship between DV and childhood temperament. Methods . Information about the voiding behaviors and temperaments of 50 children was examined using a case–control model. Caregivers were asked to fill out the Children's Behavior Questionnaire in order to rate their child on the dimensions of surgency, negative affect, and effortful control. The relationship between DV and these dimensions was then evaluated. Results . Males with DV were found to have lower effortful control than males with normal voiding habits. Females with DV did not demonstrate a difference in effortful control, but did demonstrate a higher rate of surgency. Conclusions . The results suggest that temperament does have an association with DV. These findings are in line with temperamental associations with other externalizing trouble behaviors and may inform potential treatment strategies for DV.